Теплоотводящая поверхность с пластинчато-просечным оребрением при низкоскоростном обдуве - Pismenniy, E. N.; Rogachev, V. A.; Baranuk, A. V.; Tcvyachenko, E. V. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The methodology and results of an experimental study of the thermal efficiency of new surfaces with plate-perforated fins under conditions of airflow generated by a low-pressure axial fan are presented. The efficiency of the proposed surfaces is analyzed in comparison with experimental data for plate-finned surfaces. The influence of airflow direction on the thermal efficiency of the surfaces is demonstrated.